Deletion of Type 3 Adenylyl Cyclase Perturbs the Postnatal Maturation of Olfactory Sensory Neurons and Olfactory Cilium Ultrastructure in Mice - Zhang, Zhe; Yang, Dong; Zhang, Mengdi; Zhu, Ning; Zhou, Yanfen; Storm, Daniel R.; Wang, Zhenshan (Frontiers in Cellular Neuroscience, 2017)
Type 3 adenylyl cyclase (Adcy3) is localized to the cilia of olfactory sensory neurons (OSNs) and is an essential component of the olfactory cyclic adenosine monophosphate (cAMP) signaling pathway. Although the role of this enzyme in odor detection and axonal projection in OSNs was previously characterized, researchers will still have to determine its function in the maturation of postnatal OSNs and olfactory cilium ultrastructure. Previous studies on newborns showed that the anatomic structure of the main olfactory epithelium (MOE) of Adcy3 knockout mice (Adcy3−/−) is indistinguishable from that of their wild-type littermates (Adcy3+/+), whereas the architecture and associated composition of MOE are relatively underdeveloped at this early age. The full effects of sensory deprivation on OSNs may not also be exhibited in such age. In the present study, following a comparison of postnatal OSNs in seven-, 30-, and 90-day-old Adcy3−/− mice and wild-type controls (Adcy3+/+), we observed that the absence of Adcy3 leads to cumulative defects in the maturation of OSNs. Upon aging, Adcy3−/− OSNs exhibited increase in immature cells and reduction in mature cells along with elevated apoptosis levels. The density and ultrastructure of Adcy3−/− cilia were also disrupted in mice upon aging. Collectively, our results reveal an indispensable role of Adcy3 in postnatal maturation of OSNs and maintenance of olfactory cilium ultrastructure in mice through adulthood.